2014
DOI: 10.1542/peds.2014-2541
|View full text |Cite
|
Sign up to set email alerts
|

Fighting for the Next Generation: US Prematurity in 2030

Abstract: Preterm birth (PTB) is a serious problem, with >450 000 neonates born prematurely in the United States every year. Beginning in 1980, the United States experienced a nearly 3-decade rise in the PTB rate, peaking in 2006 at 12.8%. PTB has declined for 7 consecutive years to 11.4% in 2013, but it still accounts for 1 in 9 neonates born every year. In addition to elevated neonatal and infant mortality among those born preterm, many who survive will have lifelong morbidities and disabilities. Because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 27 publications
(22 reference statements)
1
43
0
Order By: Relevance
“…This difference in part has been attributed to LMP-based dating as compared with use of ultrasonography-based estimates. 15 Although this study evaluated data from only a single year, similar results were observed in 2010 and 2011, and previous studies of earlier years have observed a similar difference between GA estimates. 6,11 These data, as well as the results from previous studies, suggest that the higher rate of preterm birth in the US may be due at least in part to the methods used to estimate prematurity, rather than a true difference in incidence.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This difference in part has been attributed to LMP-based dating as compared with use of ultrasonography-based estimates. 15 Although this study evaluated data from only a single year, similar results were observed in 2010 and 2011, and previous studies of earlier years have observed a similar difference between GA estimates. 6,11 These data, as well as the results from previous studies, suggest that the higher rate of preterm birth in the US may be due at least in part to the methods used to estimate prematurity, rather than a true difference in incidence.…”
Section: Discussionsupporting
confidence: 82%
“…These data support the recent announcement that beginning with the release of 2014 birth year data, NCHS plans to report preterm birth rates using GA measurements based on obstetric estimates. 15 Supplementary Information accompanies the paper on the Journal of Perinatology website (http://www.nature.com/jp) …”
Section: Discussionmentioning
confidence: 99%
“…Although survival of extremely preterm infants has increased over the past 2 decades, including survival without major morbidity, the individual and societal burden of preterm birth remains substantial, 43 with approximately 450,000 neonates born prematurely in the United States each year. 44 To truly impact newborn outcomes, a comprehensive and sustained effort to reduce the high rates of preterm birth is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth is recognized as a critical public health concern and, in addition, reflects persistent health disparities, being more prevalent among women of lower income status and from racial/ethnic minorities (Bryant et al 2010). Although the national PTB rate in the United States has declined from a peak of 12.8% in 2006 to 11.4% in 2013, the rate of decline is currently insufficient to meet the March of Dimes goal of 5.5% by 2030 (McCabe et al 2014). Reducing rates of PTB is important to prevent not only neonatal complications such as respiratory distress syndrome, sepsis, and intraventricular hemorrhage, but also adverse psychological, behavioral, and educational outcomes in later life, mostly related to cerebral palsy and neurodevelopmental delay (Saigal and Doyle 2008).…”
Section: Introductionmentioning
confidence: 99%